Legal identity and access to the state in South Africa - Aimable Nsabimana; Michelle Pleace; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Legal identity is an important aspect of securing access to public services, such as education, healthcare, and social protection services, including child support grants. In the South African context, in the post-apartheid period, many poor South Africans benefited from wellorganized civil registration services thanks to the systematic use of identity documents (ID), which reflect citizen registration in the country. South Africa today is considered to be a model in this area, with comparatively high levels of birth registration (near 90%). On the other hand, some populations in South Africa remain unregistered and without the necessary documentation. In particular, since the 1990s, South Africa has received major inflows of refugees, asylum seekers, and job-seeker migrants from other African countries and outside the continent. Using various survey datasets and reports, this paper documents the nature of legal identity and access to public services by migrants, and identifies plausible challenges they face in obtaining these resources.
Keywords: F22; I38; J15; J61; 330; access to public services; migration; South Africa